“I had a big revelation”: Student Experiences in Community- First Community-Campus Engagement (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2019)
While there is a wealth of literature on community-campus engagement (CCE) that incorporates student perspectives from course-based community service learning settings, the stories of students involved in longer-term CCE projects remain underexplored. This paper addresses this gap by examining the experiences of students working as research assistants (RAs) within a multi-year Canadian CCE project, “Community First: Impacts of Community Engagement” (CFICE). Drawing on interviews with RAs, student insights from a general evaluation of the CFICE project, and the authors’ own reflections, we consider the ways in which meaningful, long-standing engagements with community partners as part of community-first CCE projects provide students with both enhanced opportunities and challenges as they navigate the complexities of intersecting academic and community worlds. Further, this paper identifies promising practices to improve student experiences and the overall impact of longer-term community-campus partnerships and program management structures.